Modos de apresentação de si no Facebook: construção da identidade de jovens estudantes em um site de rede social digital - Hiller, Marcos Roberto (2014)
In a world guided by cyberculture and consumption society, in which the media contribute to shaping identity practices, we see a significant portion of young people who, through the production of content in digital social networks, share their ways of being and living. We investigated the construction of these identities by college students of two institutions of higher education in the city of São Paulo with contrasts in socioeconomic levels. Through empirical research with netnographic character, supplemented by personal interviews, it proposes an understanding of the connections between communication and consumption in the logical construction of identities within the virtual environment of digital network Facebook. The results showed that there are differences and similarities between the strategies of identity construction; however, the differences between the strategies of appropriation of social network are the most noticeable. In this investigation journey, they deserve our reflection.